Estimation of effective radiation dose for households living in rare earth mines in Nam Xe, Lai Chau province - Nguyen, Van Dung; Dao, Dinh Thuan; Nguyen, Hao Quang (Nuclear Science and Technology, 2018)
According to the United Nations Scientific Council on the Effects of Atomic Radiation (UNSCEAR), the global average dose level for the community is 2.4mSv/year. People living in the areas with high levels of radiation will cause adverse effects on their health. There are two main components that cause the dose of radiation, mainly due to the inhalation of radon and the extra dose of gamma radiation. The paper presents the results of assessment of natural effective radiation doses on the basis of the projected outpatient dosimetry in 70 households living in Mau and Mo village of Nam Xe, Phong Tho distrist, Lai Chau province.